New World Stephanocampta (Hymenoptera: Mymaridae)—descriptions of a new species from Argentina and of the male of S. masoni - Aquino, Daniel A.; Triapitsyn, Serguei V. (Zootaxa, 2014)
The genus Stephanocampta Mathot (Hymenoptera: Mymaridae) includes only two previously described species, S. yaosekoensis Mathot from the Democratic Republic of the Congo (Mathot 1966) and S. masoni (Yoshimoto) from Costa Rica and Panama (Yoshimoto 1990). Here we describe and illustrate a new species from Argentina based on a female, illustrate both sexes and newly describe the male of S. masoni, and provide a key to differentiate females of the three species.